Historical trends in snowmelt used for irrigation - Eva Kinnebrew; Lindsey L Sloat; Yue Qin; Steven J Davis; John T Abatzoglou; Stefan Siebert; Nathaniel D Mueller (Environmental Research: Food Systems)
Many agricultural regions rely on snowmelt runoff as a source of water for irrigation, but climate change is altering runoff dynamics, making it difficult to meet increasing irrigation water demands. It remains unclear whether irrigation water shortages are systematically occurring in snow-dependent regions across the globe. Here, we study global trends in surface runoff used to meet irrigation demands by linking rainfall and snowmelt runoff data with irrigation consumption data (1985–2020). Focusing on the most snow-dependent agricultural basins, we find that surface water runoff volumes have slightly decreased and snowmelt runoff is occurring significantly earlier in time (advancing an average of 8 d). These changes, coupled with an almost universal trend of increasing irrigation water consumption, have made snowmelt runoff less able to meet irrigation needs during crop growing seasons and increased reliance on alternative water sources (interbasin transfers or reservoirs). These results highlight potential future challenges for irrigated agriculture in snow-dependent regions.